IMPLICATIONS OF VARIOUS QIRAAH MUTAWATIRAH ON THE INTERPRETATION OF LEGAL VERSES - Umarul Faruq (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This article discusses the implications of the variety of mutawatirah qiraah on the interpretation of legal verses. The Qur'an, viewed from a historical perspective, cannot be separated from the various ways of reading or aspects of qiraah. Starting from the emergence of different versions of readings that were influenced by differences in Arab dialects at that time, then Uthman bin Affan took steps to copy the Qur'an as a form of maintaining the authenticity of the manuscript. History records that the differences in the readings of the companions at that time were in accordance with what was taught by the Prophet Muhammad Saw. However, scholars agree that there are several qualifications for the quality of qiraah, such as mutawatirah qiraah, masyhurah qiraah, and syadzah qiraah. The diversity of qiraah cannot be denied its existence which indirectly has implications for interpretation. Both determine the quality of an interpretation-deriving of fiqh law. This research uses a literature study model.